Food system(s), culture and community health in an Andean region of Argentina - Arrueta, Patricia Marisel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Food in the Quebrada de Humahuaca, in the province of Jujuy, is one of the region’s heritage assets that has suffered the greatest variability due to new production models that have modified the traditional consumption pattern. Industrialised products have been progressively incorporated into the diet, impacting on the native nutritional value. This work analyses the dimensions of the food systems of the ravine, with the aim of understanding the cultural contexts of production, consumption, preferences and their relationship with health risks from the point of view of its inhabitants, using a mixed territorial methodological approach.